Physiological profiles of elite parachute regiment infantry boxers. - Brown, L.; Galbraith, A.; Doyle, G.; Hastings, K. (Journal of Australian Strength and Conditioning, 2020)
Competitive boxing involves two combatants, matched in both mass and fight experience, with the aim to stop the opponent by technical or full knock out, invoke concussion, by striking with the upper extremities to the body or head to score points to win. Army boxing competitions are sanctioned by England boxing and consist of three rounds of two minutes with one-minute restorative periods. The Parachute Regiment (PR) are renowned for their mental aptitude and robustness as an elite infantry fighting force; this may be the reason for their continued success in the army boxing championships. Other studies have focused on civilian demographics, where it shows for the need for superior physiological attributes for success in competition. This study aimed to collect and identify the physiological parameters that are required to produce winning performances in an army boxing competition.